2016
DOI: 10.4103/1596-3519.188889
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy at a tertiary healthcare facility in Southwest Nigeria: Spectrum of indications and colonic abnormalities

Abstract: Background and Aim:Colonoscopy is considered the gold standard for diagnosing structural colonic diseases. It is safe and effective both for diagnosis and therapeutic interventions. This study was carried out to evaluate the pattern of indications and spectrum of colonic disease at a tertiary healthcare facility in Southwest Nigeria.Patients and Methods:All consenting patients who were referred for colonoscopy were recruited into the study. A proforma was used to record information such as biodata of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…Surprisingly, diverticular disease, which is more common to western population attributable to a low residue diet pattern, was the 3rd leading pathology recorded in our metropolitan study. Results of similar studies confirm a shift in the epidemiology of this disease in Africa [9,10,20]. It is note-worthy that no case with clinical suspicion or endoscopic diagnosis of ischaemic colitis was observed in this study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Surprisingly, diverticular disease, which is more common to western population attributable to a low residue diet pattern, was the 3rd leading pathology recorded in our metropolitan study. Results of similar studies confirm a shift in the epidemiology of this disease in Africa [9,10,20]. It is note-worthy that no case with clinical suspicion or endoscopic diagnosis of ischaemic colitis was observed in this study.…”
Section: Discussionsupporting
confidence: 71%
“…These negative results were as valuable as the positive observations as it provided relief to both the patient and the managing physician [8]. Some studies from different parts of Nigeria have reported diagnostic yield between 70% to 80% [9,10]. In Egypt and Iran, reports of 72% and 65% diagnostic yield respectively have been recorded for colonoscopy [11,12].…”
Section: Discussionmentioning
confidence: 94%
“…The commonest indication for colonoscopy was bleeding per rectum in 33.3% followed by haemorrhoids (24.8%) and suspicion of lower GI malignancy (24.3%) in this study. Bleeding per rectum was also the commonest indication in other studies in Nigeria and other parts of the world [7][8][9][10][11][12]. This may be due to the fear that is associated with passing blood from the anus which sensitize the patients that something is not right and make the patients to seek immediate medical help.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States adult population (18years and above), the overall prevalence of Inflammatory bowel disease was 478.4 per 100,000 people in 2016; the prevalence rates of Ulcerative Colitis and Crohn's Disease were 181.1 per 100,000 people and 197.7 per 100,000 people respectively [3] . Ulcerative colitis is reportedly rare in Black Africans [4,5] and indeed Nigerians [6,7,8] compared to Western populations [9,10,11] . There is no national data on the prevalence of Ulcerative Colitis in Nigeria; only few reports are available, mainly as case reports and case series [12,13,14,15] .…”
Section: Gastroenterology and Hepatology Researchmentioning
confidence: 99%